Application of an auditory steady-state response test to evaluate the attenuation of hearing protection devices - Queiroz, James Luizar de [UNESP]; Fernandes, João Candido [UNESP] (My University, 2014)
This research aims to present a new method to get real attenuation of hearing protection devices, with good reproducibility and a small standard deviation, without relying on skills and cooperation individual. Thus the authors performed tests in 10 individuals without protection and after with two kinds of ear protections (ear plug and ear muffs), to get the threshold limit value in each of the 3 stages. For this, the research used an electrophysical exam, normally used in speech therapy, named ASSR (auditory steady-state response). The principle of this exam is put on individual’s head 3 electrodes, to capture electrical signs directly in auditory nerve. In summary, the authors presented the final results. The method proposed by ANSI (American National Standards Institute) indicated an attenuation of 27.6 dB for ear plugs, while the value found in this work was 16 dB; and for ear muffs, the ANSI method indicated 29.8 dB while the value found here was 28.5 dB.
Keywords: Hearing protection; Sound attenuation; Subjective and objective hearing protection evaluation method; Hearing protection devices; ASSR (auditory steady-state response)